TASVIRLARNI SIQISH - Dalibekov.I.R,; Nomonjonov Doniyorbek Xalimjon o’gli, (TADQIQOTLAR, 2025)
Annotation: This article provides a brief overview of the main algorithms used for compressing digital images. It discusses lossless and lossy compression methods, their advantages and disadvantages, as well as the criteria for selecting compression algorithms. Information about modern trends and new compression standards is also provided. The article suggests the key aspects to focus on for effective compression of digital images